PERANCANGAN APLIKASI ABSENSI DAN PENCATATAN NILAI BERBASIS ANDROID - zulkifli zulkifli; Suhendra Suhendra; Muhammad Muslihuddin; Donny Muda Priyangan (Jurnal informasi dan komputer, 2018)
Absence is an activity or routine by a teacher or lecturer to prove that the student is present or not in a class or meeting. There are some obstacles that occur in the recording and reporting absentee written manually, such as the error of writing the name, there is a column that missed or forgot to record the date and lost or rain because the form of paper, and so forth. Therefore, researchers build an online attendance application that uses Android. This research produces an Attendance application and an online value record based on Android